Preserving Our Structures through Structural Health Monitoring - Thambiratnam, D.P. (University of Jaffna, 2022)
Civil structures such as bridges, buildings, dams, etc., are normally designed to have long life spans. However, changes in load patterns, deterioration with age and environmental effects may initiate damage in these structures. Structural Health Monitoring (SHM) has emerged as an efficient means of evaluating the health of a structure and detect damage. Structural failure can be prevented if damage is detected at its onset and appropriate retrofitting carried. Vibration based (VB) SHM methods have attracted much attention in recent times. The principle of VB methods is that the modal parameters (natural frequencies and mode shapes) of a structure change when the structure is damaged. These variations can hence be used to detect structural damage. Sophisticated instrumentation and numerical methods have enabled the rapid growth in VB SHM research and its applications to structures in which the onset of damage can be easily missed as it is not easily visible or accessible. This paper presents the basics of VB SHM and the research carried out by the author and his team on its applications to a variety of structures. They include (i) beams which are important flexural members in buildings and bridges, (ii) suspension bridge (iii) arch bridge, (iv) dam and (v) hyperbolic cooling tower.
Keywords: Structural health monitoring; Vibration data; Beams; Bridges; Dam